If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x^2-3x+5=x+25+11
We move all terms to the left:
6x^2-3x+5-(x+25+11)=0
We add all the numbers together, and all the variables
6x^2-3x-(x+36)+5=0
We get rid of parentheses
6x^2-3x-x-36+5=0
We add all the numbers together, and all the variables
6x^2-4x-31=0
a = 6; b = -4; c = -31;
Δ = b2-4ac
Δ = -42-4·6·(-31)
Δ = 760
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{760}=\sqrt{4*190}=\sqrt{4}*\sqrt{190}=2\sqrt{190}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-4)-2\sqrt{190}}{2*6}=\frac{4-2\sqrt{190}}{12} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-4)+2\sqrt{190}}{2*6}=\frac{4+2\sqrt{190}}{12} $
| 32×x=192 | | 50-x=41 | | 3/4x-2+1/3x=x-1/6 | | 8y-16-16=16 | | x÷-12=34 | | 3m-5=3m+7 | | 3x+25=77 | | 8y-1616=16 | | r2+2r-24=0 | | .6m+1.5=4.8 | | 6x+12-4x=30 | | 1.25=x/6.5 | | 6r−r=15 | | 2(3+5x)=46 | | 18y+2=36 | | 5x+3(2x–8)=42 | | 4.9x^2+12x-80=0 | | 75+5x=25+7x | | 7b-2/5=6b-7/ | | 4.9x^2+12x+80=0 | | -8v+3(v-4)=18 | | 40=0.5r | | 2t-11=4t=5 | | 1/2(50+15x-10)=8x+15 | | 4y+2y-4=8 | | c/3+9=18 | | 1=-9m+8 | | 3v+8+9v=-70 | | -62=9b-8 | | 5x-5=6.3 | | 5(m-3)=4(m-6)m= | | 4+5x=3x-76 |